[Aerial View of Cal Poly] (1957)
Aerial of Cal Poly campus, views of Engineering East, Dexter Library, Administration Building, Poly Vue Housing, North Mountain, Science Building, Spanos Stadium, agricultural Engineering, Power Plant, Poly "P" - looking east, View of the P